Sociotechnopreneurship As An Alternative For Community Empowerment In Improving The Economy Of Sugar Palm Farmers In Lonuo Village Gorontalo Province - Hasanuddin; Mardin, Herinda; Taan, Hapsawati; Salimi, Yuszda K.; Rahmatia (Yayasan Ahmar Cendekia Indonesia, 2023)
economic perspective which can become the main livelihood of the Lonuo village community so that the bioethanol center is a solution to this problem, because the production results can be used to make alcohol which is used for the cosmetics industry. , medicines The method of implementing this program is mentoring through social education activities aimed at providing social strengthening for the sugar palm farming community by providing social motivation Sociotechnopreneurship. Sociotechnopreneurship social motivation activities provide knowledge and insight to the people of Lonuo village to carry out entrepreneurship in turning palm sap into bioethanol products with the awareness that challenges need to be faced by developing ideas, having the ability to create something new, and even being able to escape from the habit of making palm sap into minimum illegal products are prohibited. Through this activity, there was an increase in the insight of the palm farmer participants regarding socio-technopreneurship in managing palm sap.